التدين وعلاقته بقلق الموت لدى المرضى المزمنين - عمامرة, سميرة; طعبلي, محمد الطاهر (University of Eloued جامعة الوادي, 2017)
هدفت الدراسة إلى الكشف عن علاقة التدين وقلق الموت لدى المرضى المزمنين ، اعتمدت على المنهج الوصفي الارتباطي، وطبقت الدراسة على عينة قوامها 342 مريضا مصاب بمرض مزمن تمّ اختيارهم بطريقة عشوائية، حيث اشتملت على 133 ذكور و209 اناث ماكثين بالمؤسسة الاستشفائية العمومية الجيلاني بن عمر بولاية الوادي. وقد استخدمت الدراسة مقياسين: مقياس التديّن للدكتور فيصل القريشي(2015) ومقياس قلق الموت من اعداد الباحثة وللتحقق من فرضيات الدراسة تمّ استخدام الأساليب الإحصائية بتطبيق نظام الحزمة الاحصائية للعلوم الاجتماعية The study aimed to uncover the relationship between religiosity and death anxiety in chronic patients. In order to reach the goals; The study was based on a descriptive approach. The study was applied to a sample of 342 chronically ill patients who were randomly chosen, which included 133 males and 209 females at the General Hospital of Jilali Ban Omar in Eloued. The study made use of two measures: the religiosity measure of Dr. Faisal Al-Quraishi (2015) and the measure of death anxiety by the researcher. In order to verify the hypotheses of the study, statistical methods were used to implement the statistical package system for social sciences: The study found the following results: - The prevalence of religiosity among people with chronic diseases is high. - The prevalence death anxiety among people with chronic disease is low. - There is an inverse correlation between religiosity and death anxiety in chronic patients.
Religiosity and its Relation to Anxiety Death in Chronic Patients
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: التدين- قلق الموت; :religiosity, death anxiety, chronic patients